Kepatuhan Minum Obat Hipertensi Pada Lansia Melalui Edukasi Peer Support di Wilayah Kerja Puskesmas Wolomarang Kabupaten Sikka - Agustina Sisilia Wati Dua Wida; Yosephina M.H Keytimu (Peneliti.net, 2022)
Peer support education is a form of independent nursing action to help people with hypertension, both individuals, groups and communities through learning activities that require support from family, peers, medical personnel and the surrounding environment so that the elderly who suffer from hypertension become obedient to taking medication because Medication adherence is one of the main supporting factors for achieving the therapeutic effect of hypertension treatment. support from family or people around them can be given in the form of emotional support, appreciation, instrumental and information. This study aims to analyze the effect of peer support education on adherence to taking hypertension medication in the elderly in the Wolomarang Health Center work area. The design of this study used a one group pre-post test design. The population in this study were all elderly people with hypertension in Wuring Village, Wolomarang Health Center Work Area. The sample size in this study was 20 respondents using a total sampling technique that met the inclusion and exclusion criteria. The independent variable in this study was Peer Support Education, while the dependent variable was adherence to taking hypertension medication. Statistical analysis using the Wilcoxon Signed Rank Test with a significance level of = 0.05. The results showed that there was an effect of peer support education on adherence to taking hypertension medication in the Wolomarang Health Center work area (p = 0.009). Therefore, considering the importance of family support, medical personnel and the people around them, it is hoped that they will continue to provide Peer Support education to the elderly so that they become obedient in taking hypertension medication. Non-adherence of hypertensive patients in taking medication can increase morbidity, mortality, and treatment costs.